Effectiveness of Cooperative Learning STAD to the Physics Learning Achievement from Achievement Motivation of High School Students - Budi Nurani (Universitas Negeri Malang, 2014)
Efektivitas Pembelajaran Kooperatif Model STAD terhadap Prestasi Belajar Fisika Ditinjau dari Motivasi Berprestasi Siswa SMA Abstract: The aim of this study is to determine the effectiveness of cooperative learning model of STAD in improving the student achievement compared to conventional learning, knowing the effectiveness of cooperative learning model of STAD than conventional learning to improve learning achievement for students with high achievement motivation, and determine the effectiveness of cooperative learning model of STAD compared to conventional learning to improve learning achievement for students with low achievement motivation. This study uses a quasi-experimental design with a 2 x 2 factorial design of study population is all students of class X SMA Negeri 3 Malang. Sampling is done randomly. Of the total students, it is divided into 8 parallel classes, four classes were sampled. The sample of 4 classes, two classes are used as experimental class learning with cooperative learning STAD model, and 2 classes as control class learning with conventional learning. Results of the study are: (1) The cooperative learning model of STAD no more effective than conventional learning to improve student achievement, (2) cooperative learning STAD model is more effective than conventional learning to improve student achievement that have high achievement motivation, (3) learning model of cooperative STAD is not more effective than conventional learning to improve student achievement that have low achievement motivation. Key Words: STAD model cooperative learning approach, achievement motivation, academic achievement Abstrak: Tujuan penelitian ini adalah untuk mengetahui efektivitas pembelajaran kooperatif model STAD dalam meningkatkan prestasi belajar siswa dibandingkan pembelajaran konvensional, mengetahui efektivitas pembelajaran kooperatif model STAD dibandingkan pembelajaran konvensional dalam meningkatkan prestasi belajar untuk siswa yang memiliki motivasi berprestasi tinggi, dan mengetahui efektivitas pembelajaran kooperatif model STAD dibandingkan pembelajaran konvensional dalam meningkatkan prestasi belajar untuk siswa yang memiliki motivasi berprestasi rendah. Penelitian ini menggunakan rancangan quasi experiment dengan desain faktorial 2 x 2. Populasi penelitian ini adalah seluruh siswa kelas X SMA Negeri 3 Malang. Pengambilan sampel dilakukan secara acak. Dari keseluruhan siswa yang terbagi menjadi 8 kelas paralel, 4 kelas diambil sebagai sampel. Dari 4 kelassampel tersebut, 2 kelas digunakan sebagai kelas eksperimen yang belajar dengan pembelajaran kooperatifmodel STAD, dan 2 kelas sebagai kelas kontrol yang belajar dengan pembelajaran konvensional. Hasil penelitian adalah: (1) pembelajaran kooperatif model STAD tidak lebih efektif dibandingkan pembelajaran konvensional untuk meningkatkan prestasi belajar siswa, (2) pembelajaran kooperatif model STAD lebih efektif dibandingkan pembelajaran konvensional untuk meningkatkan prestasibelajar siswa yang memiliki motivasi berprestasi tinggi, (3) pembelajaran kooperatif model STAD tidak lebih efektif dibandingkan pembelajaran konvensional untuk meningkatkan prestasi belajar siswa yang memiliki motivasi berprestasi rendah. Kata kunci: pendekatan pembelajaran kooperatif model STAD, motivasi berprestasi, prestasi belajar